2017
DOI: 10.1159/000480358
|View full text |Cite
|
Sign up to set email alerts
|

Independent Risk Factors and 2-Year Outcomes of Acute Kidney Injury after Surgery for Congenital Heart Disease

Abstract: Background: Data are limited regarding risk factors for acute kidney injury (AKI) following cardiac surgery in children with congenital heart disease (CHD). This observational study was performed to examine temporal trends in AKI incidence according to the Pediatric Risk, Injury, Failure, Loss, End-Stage Renal Disease (pRIFLE) criteria, identify independent risk factors for AKI after cardiac surgery, and examine associations between AKI and long-term mortality. Methods: We retrospectively evaluated 418 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 25 publications
3
36
1
2
Order By: Relevance
“…The 1.8% rate of requiring RRT is consistent with the 1–5% that was previously reported [ 22 ]. Potential preoperative and intraoperative factors contributing to the difference in AKI frequency [ 23 ], such as younger age, small body size, higher RACHS-1 score and CPB strategy were matched 1:1 by the propensity score between patients who had AKI and those who did not. We found that patients with AKI still had higher intraGF after propensity matching the above variables.…”
Section: Discussionmentioning
confidence: 99%
“…The 1.8% rate of requiring RRT is consistent with the 1–5% that was previously reported [ 22 ]. Potential preoperative and intraoperative factors contributing to the difference in AKI frequency [ 23 ], such as younger age, small body size, higher RACHS-1 score and CPB strategy were matched 1:1 by the propensity score between patients who had AKI and those who did not. We found that patients with AKI still had higher intraGF after propensity matching the above variables.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an association between duration of CPB or cross clamp and AKI was found only after surgery 2. Many earlier studies reported that longer CPB duration was a major risk factor for AKI, conferring up to 7 times greater odds if CPB duration was greater than 180 minutes (4,11). Contrarily, a lack of association between CPB duration and AKI has been found by several other groups (15,25,26).…”
Section: Discussionmentioning
confidence: 97%
“…Several well described risk factors for AKI include younger age at surgery, single ventricle physiology, surgical complexity, and cardiopulmonary bypass (CPB) duration (1,2,4,6). CPB-associated AKI, irrespective of the cause, is associated with increased morbidity, including post-operative infection (7,8), increased duration of mechanical ventilation, hospital length of stay, and increased mortality (1,3,4,6,(9)(10)(11)(12)(13). These all lead to increased hospital costs (14).…”
Section: Introductionmentioning
confidence: 99%
“…Hu and colleagues using either the RIFLE (Risk, Injury, Failure, Loss, End-Stage Renal Disease, based on serum creatinine, urine output and/or glomerular ltration rate, GFR), AKIN (Acute Kidney Injury Network, based on serum creatinine and not on GFR changes), or KDIGO (Kidney Disease: Improving Global Outcomes) criteria (combining the differences between the RIFLE and AKIN) have estimated a global incidence of AKI after cardiac surgery at 22.3% [1]. Based on the pRIFLE (Pediatric Risk, Injury, Failure, Loss, End Stage Renal Disease) criteria, AKI developed postoperatively in 24.9% of the patients [3], and de ning AKI by the KDIGO criteria revealed that 42% of the patients included in the respective study met the diagnostic criteria for AKI [4].…”
Section: Introductionmentioning
confidence: 99%